Perancangan UI/UX Sistem Informasi Perpanjangan Surat Tanda Nomor Kendaraan Menggunakan Metode Design Thinking (Kasus Samsat Kota Kendari) - Pamula, Bonifasis; Bangkalang, Dwi Hosanna (STIKOM Tunas Bangsa Pematangsiantar, 2024)
SAMSAT (One-Stop Administration System) is one of the services with a series of services in activities aimed at identification to registration of motor vehicles. Through the service of extending the Motor Vehicle Number Certificate (STNK) provided both in offices and vehicles operating around, several obstacles were found related to the service process carried out, such as: the lack of information related to the completeness of files in extending STNK which makes visitors' time when managing STNK renewal erratic, causing queues. Based on these obstacles, the author conducted research on the topic of UI / UX Design of Motor Vehicle Number Extension Information System at SAMSAT Kendari City with the aim of designing a UI / UX Information System for Extension of Motor Vehicle Number Certificate Online. This design process requires a survey related to users to focus the problem so as to be able to define new ideas based on the solutions obtained, therefore this research will use the Design Thinking method. The stages in carrying out the Design Thinking method consist of 5 stages, namely: Empathize, Define, Ideate, Prototype, and Testing so as to assist the author in conducting research starting from the first stage of distributing questionnaires, finding and identifying problems, providing solution ideas, making prototype designs, to simulating prototypes using Single Ease Questions (SEQ) consisting of values 1 to 7 as an assessment tool from the user's point of view in running. interact with the system. The conclusion of this study obtained an average score on prototype testing between 5.32 to 6.66 from 50 related respondents. It can be stated that the resulting design can be accessed easily and answer the needs of the user.